2018
DOI: 10.21037/acs.2018.07.01
|View full text |Cite
|
Sign up to set email alerts
|

Is there a role for fractional flow reserve in coronary artery bypass graft (CABG) planning?

Abstract: The concept of significant lesions has substantially evolved over the last decade. With growing evidence for use of fractional flow reserve (FFR) as a determinant of lesion-specific ischemia and its superiority to angiography-guided revascularization and medical therapy, the field of percutaneous revascularization has shifted to rely exclusively on FFR instead of luminal stenosis alone in guiding revascularization. This transition to physiological assessment has not yet made it to the realm of surgical revascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…The patients most deserving of physiological guidance are those with multivessel disease being considered for CABG. 17 However, very few receive pressure wire assessment prior to CABG, and often, referral for surgery is based on a CAG performed in a non-interventional CCL. Further guidance with FFR would require a second visit to a CCL, with associated delays, and is therefore rarely done.…”
Section: Coronary Artery Bypass Surgery (Cabg): a Major Unmet Need For Physiological Guidancementioning
confidence: 99%
“…The patients most deserving of physiological guidance are those with multivessel disease being considered for CABG. 17 However, very few receive pressure wire assessment prior to CABG, and often, referral for surgery is based on a CAG performed in a non-interventional CCL. Further guidance with FFR would require a second visit to a CCL, with associated delays, and is therefore rarely done.…”
Section: Coronary Artery Bypass Surgery (Cabg): a Major Unmet Need For Physiological Guidancementioning
confidence: 99%
“…As such, suboptimal medical management in CABG as shown in many randomized trials needs further optimization by means of adopting recent guidelines recommendations [63,64]. To further improve outcomes in CABG, recent trends of preoperative conditioning by means of improving the functional capacity through multimodal prehabilitation (preoperative rehabilitation) programs need further attention [65].…”
Section: Primary and Secondary Prevention Prehabilitationmentioning
confidence: 99%
“…In patients with stable coronary artery disease, an invasive haemodynamic evaluation such as fractional flow reserve (FFR) is recommended in the absence of documented ischemia at non‐invasive imaging testing in order to decide if a stenotic vessel needs to be revascularized or not 1,2 . In the field of percutaneous coronary intervention (PCI), randomized clinical trials demonstrated the benefit of FFR‐guidance 3‐9 but the level of evidence is not as high in the field of surgical revascularisation 10 . Retrospective data suggest that ‐ as compared to angiography‐guided coronary artery bypass graft (CABG) surgery ‐ FFR‐guided CABG surgery is associated with a simplified surgical intervention and with a higher graft patency rate at 6 years, 11 leading to a significantly lower rate of overall death and myocardial infarction 12 .…”
Section: Introductionmentioning
confidence: 99%
“…1,2 In the field of percutaneous coronary intervention (PCI), randomized clinical trials demonstrated the benefit of FFR-guidance [3][4][5][6][7][8][9] but the level of evidence is not as high in the field of surgical revascularisation. 10 Retrospective data suggest that -as compared to angiography-guided coronary artery bypass graft (CABG) surgery -FFR-guided CABG surgery is associated with a simplified surgical intervention and with a higher graft patency rate at 6 years, 11 leading to a significantly lower rate of overall death and myocardial infarction. 12 More recently, in the single-blinded prospective multicenter randomized controlled trial for FFR-guided versus angiography-guided CABG (GRAFFITI) trial, FFR-guided CABG was also associated with a significantly simplified surgical procedure without impact on 1-year graft patency.…”
mentioning
confidence: 99%